Optimizing Distribution Center Network Design for a Cosmetic Manufacturer: A Case Study on Lightening Series Package Product - Kusumawardani, Rindi; Rehaldy, Aufa Rais; Savitri, Niken Anggraini (Universitas Muhammadiyah Sidoarjo, 2024)
Ensuring customer satisfaction while maintaining optimal cost efficiency is paramount in designing a successful supply chain structure. This study explores the vital role of service quality and delivery efficiency in achieving customer satisfaction and a superior overall experience through a cost-effective supply chain structure. Furthermore, the strategic positioning of Distribution Centers (DC) and the geographical distribution of consumers serve as additional determinants in the quest to devise the most effective DC scheme that meets consumer expectations. Four simulation scenarios, each with measurable parameters including response time, lead time, and operational costs, were evaluated to identify the most cost-efficient and responsive solution. These parameters encompassed the performance metrics of the supply chain structure model, namely response time and lead time, in conjunction with the total operational cost of each scenario. Our findings reveal that scenario 1 emerges as the most cost-effective with the lowest distribution costs and shortest customer lead time. This scenario consistently maintains the lowest distribution costs from the first to the seventh year. Despite a surge in forecasted demand in the 7th year, resulting in an increase in total distribution costs to Rp. 3,392,793,440, scenario 1 still prevails with overall vehicle costs decreasing and the smallest percentage cost at 17.50%, thus yielding the most economical outcome compared to alternative scenarios. Scenario 4 offers a similar outcome to scenario 1 but incurs higher daily vehicle operating costs. The cost-effectiveness demonstrated by scenario 4 further highlights the significance of strategic DC placement in achieving optimal supply chain outcomes.